Pengaruh Kualitas Pelayanan, Harga Dan Tempat Terhadap Kepuasan Pelanggan Cus-Cus Café Malang - Sohib Sohib; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the Effect of Service Quality, Price and Place on Customer Satisfaction of Cus-Cus Café Malang. The variable used in this study is the customer satisfaction variable as the dependent variable, while the independent variable is Service Quality, Price and Place. Data were collected through a questionnaire method with a total sample of 92 respondents.The results of this study together conclude that there are Effects of Service Quality, Price and Place on Customer Satisfaction of Cus-Cus Café Malang and partially conclude that there is Effect of Service Quality, Price and Place on Customer Satisfaction of Cus-Cus Cafe Malang. Keywords: Service Quality, Price, Place, Customer Satisfaction